A Farnesyltransferase Acts to Inhibit Ectopic Neurite Formation in C. elegans - Carr, David; Sanchez-Alvarez, Leticia; Imai, Janice H.; Slatculescu, Cristina; Noblett, Nathaniel; Mao, Lei; Beese, Lorena; Colavita, Antonio (PLOS ONE, 2016)
Genetic pathways that regulate nascent neurite formation play a critical role in neuronal morphogenesis. The core planar cell polarity components VANG-1/Van Gogh and PRKL-1/Prickle are involved in blocking inappropriate neurite formation in a subset of motor neurons in C. elegans. A genetic screen for mutants that display supernumerary neurites was performed to identify additional factors involved in this process. This screen identified mutations in fntb-1, the β subunit of farnesyltransferase. We show that fntb-1 is expressed in neurons and acts cell-autonomously to regulate neurite formation. Prickle proteins are known to be post-translationally modified by farnesylation at their C-terminal CAAX motifs. We show that PRKL-1 can be recruited to the plasma membrane in both a CAAX-dependent and CAAX-independent manner but that PRKL-1 can only inhibit neurite formation in a CAAX-dependent manner.